Degradable visible biliary stent
By coating magnesium alloy biliary stents with titanium dioxide and using shape memory hydrogel fixtures at the connection points, the problems of mismatch of degradation time and difficulty in mechanical support of magnesium alloy are solved, and short-term biliary duct obstruction of the stent is achieved Stability and visibility during recovery period.
Patent Information
- Application Number
- CN202411219470.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-02-14
AI Technical Summary
Magnesium alloys are used for short-term biliary occlusion and are difficult to maintain mechanical support, affecting the stability of the biliary stent.
Made a mesh biliary stent with magnesium alloy coated with ceramic material containing titanium dioxide, and wraps a hydrogel fixture with shape memory function at the braided connection point to ensure that the stent maintains structural integrity and visibility during the recovery period. .
The degradation time of magnesium alloy is extended, allowing it to remain stable during the recovery period of short-term biliary occlusion, providing sufficient mechanical support, and improving intraoperative operation and postoperative monitoring through visibility.
Smart Images

Figure CN119424060A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hepatobiliary instruments, and is an instrument suitable for short-term bile duct obstruction, and in particular to a degradable visible bile duct stent. Background Art
[0002] Short-term bile duct obstruction is usually caused by gallstones, acute cholangitis and other reasons, which can lead to obstruction of bile flow, pain, infection and other complications. Compared with malignant tumors, bile duct scar stenosis and other conditions that require long-term stent support, the use of degradable biliary stents is of great significance in short-term bile duct obstruction because it can temporarily support the bile duct, restore the normal flow of bile, and relieve patient symptoms. After the bile duct heals naturally or the problem is solved by other treatments, the stent can be naturally degraded and does not require a second surgery to remove, thereby reducing the patient's pain and surgical risks.
[0003] Magnesium alloy is a biodegradable material used in biliary stents. It is biodegradable, biocompatible and has good mechanical properties. However, the main reason why it has not been clinically applied is that magnesium alloy degrades quickly and is prone to pitting corrosion, which affects the stability of the entire structure. For short-term biliary obstruction, the recovery period is usually 4-8 weeks, and the total degradation time of magnesium alloy materials is between several weeks and several months. The key to using this material is to select suitable magnesium alloys and surface treatment methods to make the degradation time of magnesium alloys after the recovery period. At the same time, since the biliary stent is a mesh structure, it is necessary to ensure the stability of the structure at the connection point, ensure that the stent can maintain the mechanical structure unchanged during the recovery period, and provide sufficient support.
[0004] In short-term biliary obstruction, in addition to the requirement for material degradability, visibility is also very necessary. If visibility can be affected, it will be very beneficial for doctors' intraoperative operations and postoperative monitoring. During the operation, it can ensure that the stent can be correctly positioned and deployed during the implantation process; after the operation, the position and status of the stent can be monitored to ensure that it will not shift during the treatment. If shifting or re-blocking occurs, it can be dealt with in time. Summary of the invention
[0005] The present invention provides a degradable visible biliary stent, which solves the problems of mismatched degradation time of magnesium alloy for short-term biliary obstruction and difficulty in maintaining continuous mechanical support. At the same time, the structure of the present invention can also construct a visible system, which is beneficial for intraoperative operation and postoperative monitoring.
[0006] The present invention is achieved through the following technical solutions: A degradable visible biliary stent, the biliary stent is a mesh stent, the mesh stent is woven from a magnesium alloy material coated with a coating, the coating is prepared from a ceramic material containing titanium dioxide, and a fixing piece of a hydrogel with a shape memory function is wrapped at the woven connection point.
[0007] Furthermore, the fixing member is a hollow pipe structure, the front and rear surfaces of which are curved surfaces, and the upper and lower ends of the left and right sides are respectively provided with grooves.
[0008] Furthermore, the method for coating the magnesium alloy is as follows: S1: Surface pretreatment: Use ethanol to ultrasonically clean the magnesium alloy sample to remove surface oil and impurities, soak the sample in 3-5% HNO3 solution for 20-60s to remove the oxide layer on the sample surface and activate the surface, thoroughly wash the sample with deionized water, and dry it naturally at room temperature; S2: Mix hydroxyapatite or tricalcium phosphate nanoparticles and titanium dioxide in a weight ratio of (3-4):1 to form a ceramic substrate, disperse the ceramic substrate in ethanol, the weight ratio of the ceramic substrate to the ethanol is 1:10, stir evenly, add polyvinyl alcohol, the weight ratio of the polyvinyl alcohol to the ceramic substrate is 1:(5-6), stir thoroughly to form a stable suspension; S3: Use a spray gun to evenly spray the suspension on the pretreated magnesium alloy surface with a spray thickness of 5-10 μm, and dry it in a vacuum drying oven at a temperature of 180-200° C. for 1.5-2 hours.
[0009] Furthermore, the preparation method of the fixing member is as follows: S21: dissolving 10-20% by mass of PEGDA and 10% by mass of PLA in deionized water; adding 0.5% of photoinitiator Irgacure 2959 and stirring until completely dissolved; adding 10-20% of PNIPAM and stirring evenly; S22: degassing the prepared solution under vacuum conditions to remove bubbles in the solution; S23: injecting the de-bubbled solution into a large-sized mold to ensure that the liquid is evenly distributed in the mold; irradiating the mold under a 365 nm wavelength ultraviolet lamp for 10-30 minutes to ensure sufficient cross-linking; S24: secondary cross-linking, the photo-cross-linked hydrogel was placed in a water bath at 37 °C for 1 h to further strengthen the structure by temperature cross-linking; S25: The formed hydrogel is heated to 70-80°C to soften it, and then stuffed into a small-sized mold under the action of external force to deform it into a desired smaller shape; the shape is maintained and quickly cooled to room temperature or a lower temperature to fix the deformed shape.
[0010] Furthermore, a plurality of evenly distributed high-purity platinum sheets are disposed inside the front curved surface of the fixing member, and a plurality of evenly arranged spherical grooves are disposed on the outer surface.
[0011] Furthermore, the spherical groove is filled with drug-loaded microspheres.
[0012] Furthermore, the preparation method of the drug-loaded microspheres is: S31: Dissolve 500 mg of PLGA in 5 mL of deionized water; dissolve 10 mg of prednisone and 10 mg of phloroglucinol in the PLGA solution respectively and stir well; S32: Dissolve 5 g of PVA in 100 mL of deionized water to prepare a 5% (w / v) PVA solution; S33: loading the PLGA drug solution and the PVA solution into two syringes respectively; connecting the two syringes to the inlet of the T-shaped microfluidic chip through a pipeline; S34: Using a syringe pump, set the flow rates of PLGA drug solution and PVA solution to 10 µL / min and 100 µL / min, respectively; generate uniform O / W emulsion droplets through the microfluidic chip; S35: Collect the generated emulsion droplets in a beaker filled with deionized water; place the beaker in a vacuum drying oven, set the temperature to room temperature, and the vacuum degree to 0.1 MPa for 4 hours to allow the aqueous phase solvent to evaporate slowly to form solid microspheres; S36: The solidified microspheres were washed with deionized water several times to remove residual PVA and unencapsulated drugs; the microspheres were separated by centrifugation at 3000 rpm for 10 minutes; the washed microspheres were placed in a vacuum drying oven, set at room temperature (25°C), vacuum degree of 0.1 MPa, and dried for 24 hours.
[0013] Furthermore, at least one position sensor or wireless transmission module is disposed inside the front curved surface of the fixing member.
[0014] Furthermore, one or two fixings on the biliary stent are fixed with a wireless transmission module.
[0015] Furthermore, an annular first fixing unit and a second fixing unit are fixed on the outer surface of the biliary stent, the second fixing unit contains a wireless transmission module, the first fixing unit contains a position sensor, and there is at least one first fixing unit.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention is made of degradable materials as a whole, and after the short-term bile duct obstruction is cured and recovered, the bile duct stent will gradually degrade; The two aspects of optimization of magnesium alloy materials maintain the integrity of the biliary stent structure during use and have anti-fouling and antibacterial effects. The degradable ceramic coating containing titanium dioxide makes the biliary stent as a whole have anti-fouling and antibacterial effects, and can also ensure that the biliary stent does not degrade during use; A fixing piece is arranged at the intersection of the braided wires of the stent, which can wrap the braided wires at that location to extend the service life of the stent, and also play an auxiliary fixing effect, so that the biliary stent can be firmly fixed in the bile duct; The fixation device can be upgraded to a functional fixation device, in which a high-purity platinum sheet is placed to make it visible to images and can be used for postoperative monitoring; At the same time, it is further upgraded to a position sensor, which no longer requires the use of imaging equipment and can be used not only for postoperative monitoring but also for intraoperative positioning. The presence of the fixing part provides space for drug administration, and a spherical groove is provided on the fixing part for storing drug-loaded microspheres; at the same time, combined with the shape memory characteristics of the fixing part, the drug can also be gradually released during the process of restoring the size. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a weight change curve diagram of the sample in the salt spray test and the Hank's simulated body fluid immersion test in Example 1 of the present invention; Figure 2 is a schematic structural diagram of a fixing member in Embodiment 2 of the present invention; Figure 3 is a schematic diagram of a fixing member in a first state in Embodiment 2 of the present invention; Figure 4 is a schematic diagram of the fixing member in the second state in Embodiment 2 of the present invention; Figure 5 is a schematic structural diagram of a functional fixing member in Embodiment 3 of the present invention; Figure 6 is a schematic diagram of a functional fixing member in a first state in Embodiment 3 of the present invention; Figure 7 is a schematic diagram of the functional fixing member in the second state in Embodiment 3 of the present invention; Figure 8 It is a schematic diagram of the installation positions of the sensors and the transmission module in Example 4 of the present invention.
[0018] Among them, 1-mesh stent, 10-woven wire, 20-drug-loaded microspheres, 100-fixing part, 110-inner curved surface, 120-outer curved surface, 130-left side, 140-right side, 150-upper groove, 160-lower groove, 200-functional fixing part, 210-first curved surface, 220-second curved surface, 230-first side, 240-second side, 250-first groove, 260-second groove, 270-high-purity platinum sheet, 280-spherical groove, 300-first fixing unit, 310-second fixing unit. DETAILED DESCRIPTION
[0019] In order to make the present invention more clearly understood, the following detailed description is given through the following embodiments in conjunction with the accompanying drawings.
[0020] The present invention is made of degradable materials as a whole. After the short-term bile duct obstruction is cured and recovered, the biliary stent will gradually degrade; during the treatment recovery period, usually within 8 weeks, the complete structure needs to be maintained.
[0021] This embodiment uses magnesium alloy material as the matrix, and uses magnesium alloy wire to weave into a mesh structure. In this embodiment, the magnesium alloy material is optimized in two aspects, the purpose of which is to maintain the integrity of the structure and to prevent fouling and antibacterial. On the one hand, the optimization is to coat the surface of the magnesium alloy material, and on the other hand, the structural parts are fixed at the intersection of the stent braiding wires (the structural parts can be fixed at each intersection or at some intersections).
[0022] The magnesium alloy materials used in this embodiment are some types commonly used in biomedicine, such as magnesium-aluminum alloy AZ31, AZ91, magnesium-calcium alloy, magnesium-zinc alloy ZK60, ZK40, magnesium-rare earth alloy WE43. These alloys have good biocompatibility and degradation characteristics.
[0023] The coating material can regulate the degradation time of the above magnesium alloy material so that it can maintain its intact structure within 8 weeks. Specifically: Take magnesium aluminum alloy AZ31 as an example: S1: Surface pretreatment: Use ethanol to ultrasonically clean the AZ31 magnesium alloy sample to remove surface oil and impurities, soak the sample in 5% HNO3 solution for 0.5-1min to remove the oxide layer on the sample surface and activate the surface, thoroughly wash the sample with deionized water, and dry it naturally at room temperature; S2: Mix hydroxyapatite and titanium dioxide in a weight ratio of 3:1 to form a ceramic substrate, disperse the ceramic substrate in ethanol, and the weight ratio of the ceramic substrate to the ethanol is 1:10. After stirring evenly, add polyvinyl alcohol (PVA), and the weight ratio of PVA to the ceramic substrate is 1:5. After fully stirring, a stable suspension is formed; S3: Use a spray gun to evenly spray the suspension on the surface of the pretreated AZ31 magnesium alloy with a spray thickness of 5-10 μm, and dry it in a vacuum drying oven at 200°C for 2 hours.
[0024] Take magnesium-zinc alloy ZK40 as an example: S11: After ultrasonic washing with ethanol, the surface of ZK40 alloy was pickled with 3% dilute nitric acid solution for 20-30 seconds, and then the sample was thoroughly washed with deionized water and dried naturally at room temperature; S12: tricalcium phosphate nanoparticles and titanium dioxide nanoparticles are mixed in a ratio of 4:1 to form a ceramic substrate, the ceramic substrate is dispersed in an ethanol solution, the weight ratio of the ceramic substrate to the ethanol is 1:10, polyvinyl alcohol is added, the weight ratio of PVA to the ceramic substrate is 1:6, and after sufficient stirring, a stable suspension is formed; S13: Use a spray gun to evenly spray the titanium dioxide-doped calcium phosphate-based ceramic suspension on the pretreated ZK40 magnesium-zinc alloy surface, control the spraying thickness to be about 5-10 μm, and place the coated sample in a vacuum drying oven to dry at a temperature of 180°C for 1.5 h.
[0025] For different alloy types, the selected reagent concentrations and dosages, and reaction conditions will be different and need to be adjusted through experiments. This embodiment only provides coating solutions for the above two alloys.
[0026] This example also passed the salt spray test (continuous salt spray corrosion test in a salt spray chamber) and the in vitro immersion test of Hank's simulated body fluid. The weight of the sample in the salt spray chamber began to decrease significantly in the 7th week and then degraded rapidly; the sample in the Hank's simulated body fluid began to decrease in weight in the 9th week and then gradually degraded. The weight change diagram is shown in the attached figure. Figure 1 shown.
[0027] On the basis of Example 1, this example is structurally optimized, and by adding structural parts, the biliary stent has better corrosion resistance and better positioning and fixing performance. Figure 2 As shown, the fixing member 100 is a hydrogel with a double network structure having shape memory, and is hollow inside and surrounded by an inner curved surface 110, a left side surface 130, an outer curved surface 120, and a right side surface 140, with a curvature in front and back, and a parallel structure on the left and right sides, as shown in FIG. Figure 3 and Figure 4As shown, the fixing member 100 is wrapped around the node where the braided wires 10 intersect, the inner curved surface 110 is located on the inner side of the mesh stent 1, and the outer curved surface 120 is located on the outer side of the mesh stent 1. There are upper grooves 150 and lower grooves 160 on the upper and lower sides of the left side 130 and the right side 140, respectively, and their function is that after the mesh stent 1 is unfolded, the braided wires 10 are stuck in the upper grooves 150 and the lower grooves 160. The fixing member 100 is a hydrogel material. In the first state, it can be wrapped around the outside of the braided wires, which plays a certain protective role on the braided wires at the intersection and avoids corrosion at this place; secondly, after implantation, the outer curved surface 120 contacts the bile duct wall, which enhances the positioning and fixation effect.
[0028] The preparation method of the fixing member in this embodiment is as follows: S21: Dissolve 10-20% by weight of PEGDA (molecular weight 600-700) and 10% of PLA (molecular weight 5000-10000Da) in deionized water; add 0.5% of photoinitiator Irgacure 2959 and stir until completely dissolved; add 10-20% of PNIPAM and stir evenly; S22: degassing the prepared solution under vacuum conditions to remove bubbles in the solution; S23: Inject the de-bubbled solution into a large-sized mold (the maximum size after the hydrogel is stretched) to ensure that the liquid is evenly distributed in the mold; irradiate the mold under a 365 nm ultraviolet lamp for 10-30 minutes to ensure sufficient cross-linking; S24: secondary cross-linking, the photo-cross-linked hydrogel was placed in a water bath at 37 °C for 1 h to further strengthen the structure by temperature cross-linking; S25: The formed hydrogel is heated to 70-80°C to soften it, and then stuffed into a small-sized mold under the action of external force to deform it into a desired smaller shape; the shape is maintained and quickly cooled to room temperature or a lower temperature to fix the deformed shape.
[0029] In order to facilitate assembly, a through opening is opened longitudinally on the curved surface 110. After the mesh stent 1 is woven, the fixing piece 100 is inserted into the intersection of the braided wires 10. Since the intersection is relatively large and after implantation, as the mesh stent 1 and the fixing piece 100 expand and unfold, the fixing piece will not fall out of the fixing piece 100.
[0030] By compounding with PLA materials, the fixing part 100 has degradable properties. During degradation, thinner parts such as the inner curved surface 110, the left side surface 130, and the right side surface 140 are prone to degrade first, and the fixing part 100 at the degradation port can flow out with the bile (the diameter of the braided wire is usually 0.1-0.2mm, and the size of the fixing part is 0.5mm-1mm after unfolding, which can smoothly flow out through the Oddi sphincter); secondly, the fixing part 100 has temperature responsiveness and shape memory functions through the PNIPAM material, which is more suitable for the unfolding speed of the biliary stent. After testing, the above-mentioned stent can be fully unfolded in about 2 minutes when placed in physiological saline at 37°C. In contrast, the stent without PNIPAM needs 5-10 minutes to be fully unfolded.
[0031] Based on Example 2, the fixing element 100 is optimized to form a functional fixing element 200. As described in the background art, for short-term bile duct obstruction, in addition to the requirement for degradation, there is also a need for visibility. Specifically, Figure 5 , Figure 6 and Figure 7 As shown, the functional fixing part 200 is a hollow structure formed by connecting and enclosing a first curved surface 210, a first side surface 230, a second curved surface 220, and a second side surface 240 in sequence. Corresponding to the embodiment, a first groove 250 and a second groove 260 are provided on the upper and lower sides of the first side surface 230 and the second side surface 240, respectively.
[0032] Different from Example 2, there are several evenly distributed high-purity platinum sheets 270 (high-purity platinum sheets refer to platinum sheets with a platinum content greater than 99.99%) inside the second curved surface 220. The high-purity platinum sheets 270 are used to achieve visibility, and their multiple small-sized distribution ensures that even if the functional fixing part 200 is degraded and the high-purity platinum sheets 270 fall out of the functional fixing part 200, their size can still flow out smoothly through bile. There are several evenly distributed spherical grooves 280 on the surface of the second curved surface 220, and the spherical grooves 280 are filled with drug-loaded microspheres 20. In the first state, most of the spherical grooves 280 are located inside the second curved surface 220, and their openings are much smaller than the diameter of the spherical grooves. At this time, even without the aid of a closed structure, the drug-loaded microspheres 20 can be maintained in the spherical grooves 280; when the functional fixing part 200 is unfolded and restored to its size, the opening of the spherical grooves 280 becomes larger, and the drug-loaded microspheres 20 are freed from the spherical grooves 280. The drug-loaded microspheres 20 that cannot be freed due to contact with the bile duct wall can also continuously release drugs on the bile duct wall.
[0033] The drug-loaded microspheres 20 in this embodiment mainly involve two types of drugs, one is an anti-inflammatory drug, such as prednisone; the other is an anti-vasospasm drug, such as phloroglucinol.
[0034] The preparation method of drug microspheres 20 is as follows: S31: Dissolve 500 mg of PLGA in 5 mL of deionized water; dissolve 10 mg of prednisone and 10 mg of phloroglucinol in the PLGA solution respectively and stir well; S32: Dissolve 5 g of PVA in 100 mL of deionized water to prepare a 5% (w / v) PVA solution; S33: Load the PLGA drug solution and the PVA solution into two syringes respectively; connect the two syringes to the inlet of the microfluidic chip (T-type) through a pipe; S34: Using a syringe pump, set the flow rates of PLGA drug solution and PVA solution to 10 µL / min and 100 µL / min, respectively; generate uniform O / W emulsion droplets through the microfluidic chip; S35: Collect the generated emulsion droplets in a beaker filled with deionized water; place the beaker in a vacuum drying oven, set the temperature to room temperature (25°C), and the vacuum degree to 0.1 MPa for 4 hours to allow the aqueous phase solvent to evaporate slowly to form solid microspheres; S36: The solidified microspheres were washed with deionized water several times to remove residual PVA and unencapsulated drugs; the microspheres were separated by centrifugation at 3000 rpm for 10 minutes; the washed microspheres were placed in a vacuum drying oven, set at room temperature (25°C), vacuum degree of 0.1 MPa, and dried for 24 hours.
[0035] In this embodiment, a microfluidic method is used to prepare drug-loaded microspheres, and an aqueous phase system is used to minimize the use of organic solvents; by adjusting the flow rate and flow ratio, microspheres of uniform size are generated, which can improve the stability of drug release, and is more suitable for the needs of short-term biliary obstruction.
[0036] The high-purity platinum sheet in this embodiment, combined with CT scanning, can determine the position of the biliary stent.
[0037] In addition to high-purity platinum sheets, the positioning and monitoring solutions can be further optimized so that they can be visible without the aid of imaging equipment. At this time, the scope of application will be wider, and it can not only be used for regular postoperative monitoring, but also for intraoperative positioning.
[0038] Continuing with the solution of Example 3, the high-purity platinum sheet is replaced with a position sensor and a wireless transmission module. Like the high-purity platinum sheet, it is wrapped inside the second curved surface 220. In order to reduce the size, the AMS AS5600 (WLCSP package) position sensor and the nRF52810 (QFN package) wireless transmission module are selected in this embodiment.
[0039] Correspondingly, there is a terminal on the outside that receives the information of the position sensor received by the wireless transmission module; at the same time, the sensor detection frequency and the wireless transmission module transmission frequency can also be adjusted to extend the use time of the sensor and the wireless transmission module. This part is the existing technology and will not be repeated here.
[0040] In addition, you can also use Figure 8 The structure shown is composed of a plurality of functional fixing parts 200 spliced together to form a first fixing unit 300 and a second fixing unit 310. The functional fixing parts 200 constituting the first fixing unit 300 contain position sensors; the functional fixing parts 200 constituting the second fixing unit 310 contain wireless transmission modules. The advantage of this structure is that it can provide a clear position line, and the spliced structure makes the space for assembling sensors and wireless transmission modules larger. In this case, the functional fixing parts 200 can no longer be spliced together, but directly form a ring-shaped whole.
[0041] The above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all implementation methods here, and these obvious changes or modifications derived from the spirit of the present invention are still within the scope of protection of the present invention.
Claims
1. A degradable visible biliary stent, wherein the biliary stent is a mesh stent, characterized in that: The mesh stent is woven from a magnesium alloy material coated with a coating, the coating is made of a ceramic material containing titanium dioxide, and a fixing piece of a hydrogel with a shape memory function is wrapped at the woven connection point.
2. A degradable visible biliary stent according to claim 1, characterized in that: The fixing piece is a hollow pipe structure, the front and rear sides of which are curved surfaces, and the upper and lower ends of the left and right sides are respectively provided with grooves.
3. A degradable visible biliary stent according to claim 1, characterized in that: The method of coating magnesium alloy is: S1: Surface pretreatment: Use ethanol to ultrasonically clean the magnesium alloy sample to remove surface oil and impurities, soak the sample in 3-5% HNO3 solution for 20-60s to remove the oxide layer on the sample surface and activate the surface, thoroughly wash the sample with deionized water, and dry it naturally at room temperature; S2: Mix hydroxyapatite or tricalcium phosphate nanoparticles and titanium dioxide in a weight ratio of (3-4):1 to form a ceramic substrate, disperse the ceramic substrate in ethanol, the weight ratio of the ceramic substrate to the ethanol is 1:10, stir evenly, add polyvinyl alcohol, the weight ratio of the polyvinyl alcohol to the ceramic substrate is 1:(5-6), stir thoroughly to form a stable suspension; S3: Use a spray gun to evenly spray the suspension on the pretreated magnesium alloy surface with a spray thickness of 5-10 μm, and dry it in a vacuum drying oven at a temperature of 180-200° C. for 1.5-2 hours.
4. A degradable visible biliary stent according to claim 1 or 2, characterized in that: The preparation method of the fixing member is as follows: S21: dissolving 10-20% by mass of PEGDA and 10% by mass of PLA in deionized water; adding 0.5% of photoinitiator Irgacure 2959 and stirring until completely dissolved; adding 10-20% of PNIPAM and stirring evenly; S22: degassing the prepared solution under vacuum conditions to remove bubbles in the solution; S23: injecting the de-bubbled solution into a large-sized mold to ensure that the liquid is evenly distributed in the mold; irradiating the mold under a 365 nm wavelength ultraviolet lamp for 10-30 minutes to ensure sufficient cross-linking; S24: secondary cross-linking, the photo-cross-linked hydrogel was placed in a water bath at 37 °C for 1 h to further strengthen the structure by temperature cross-linking; S25: The formed hydrogel is heated to 70-80°C to soften it, and then stuffed into a small-sized mold under the action of external force to deform it into a desired smaller shape; the shape is maintained and quickly cooled to room temperature or a lower temperature to fix the deformed shape.
5. The degradable visible biliary stent according to claim 2, characterized in that: The front curved surface of the fixing piece has a plurality of evenly distributed high-purity platinum sheets inside, and the outer surface has a plurality of evenly arranged spherical grooves.
6. The degradable visible biliary stent according to claim 5, characterized in that: The spherical groove is filled with drug-loaded microspheres.
7. The degradable visible biliary stent according to claim 6, characterized in that: The preparation method of the drug-loaded microspheres is as follows: S31: Dissolve 500 mg of PLGA in 5 mL of deionized water; dissolve 10 mg of prednisone and 10 mg of phloroglucinol in the PLGA solution respectively and stir well; S32: Dissolve 5 g of PVA in 100 mL of deionized water to prepare a 5% (w / v) PVA solution; S33: loading the PLGA drug solution and the PVA solution into two syringes respectively; connecting the two syringes to the inlet of the T-shaped microfluidic chip through a pipeline; S34: Using a syringe pump, set the flow rates of the PLGA drug solution and PVA solution to 10 µL / min and 100 µL / min, respectively; generate uniform O / W emulsion droplets through the microfluidic chip; S35: Collect the generated emulsion droplets in a beaker filled with deionized water; place the beaker in a vacuum drying oven, set the temperature to room temperature, and the vacuum degree to 0.1 MPa for 4 hours to allow the aqueous phase solvent to evaporate slowly to form solid microspheres; S36: The solidified microspheres were washed with deionized water several times to remove residual PVA and unencapsulated drugs; the microspheres were separated by centrifugation at 3000 rpm for 10 minutes; the washed microspheres were placed in a vacuum drying oven, set at room temperature (25°C), vacuum degree of 0.1 MPa, and dried for 24 hours.
8. The degradable visible biliary stent according to claim 2, characterized in that: At least one position sensor or wireless transmission module is disposed inside the front curved surface of the fixing member.
9. The degradable visible biliary stent according to claim 8, characterized in that: The biliary stent has one or two fixings fixed with a wireless transmission module.
10. The degradable visible biliary stent according to claim 1, characterized in that: An annular first fixing unit and a second fixing unit are fixed on the outer surface of the biliary stent, the second fixing unit contains a wireless transmission module, the first fixing unit contains a position sensor, and there is at least one first fixing unit.